A distributed optimization algorithm for the dynamic hydraulic balance of chilled water pipe network in air-conditioning system. (15th May 2021) - Yu, Junqi; Liu, Qite; Zhao, Anjun; Chen, Shiyu; Gao, Zhikun; Wang, Fu; Zhang, Rui
Abstract: Aiming at the problem of the dynamic hydraulic balance regulation of chilled water pipe network in central air-conditioning system, a distributed iterative optimization algorithm is proposed based on the novel distributed control architecture and the alternating direction method of multipliers (ADMM) with regular term. Firstly, the total flow and the minimum water pressure difference between supply and return are calculated according to the flow demand of each air handling unit. Furthermore, based on the ADMM with regular term, the optimal operation of parallel pumps is accomplished. Finally, the dynamic hydraulic balance of chilled water pipe network is achieved with the minimum energy consumption, and the on-demand flow distribution is realized. After that, a central air-conditioning system is taken as an example to verify the performance of the proposed algorithm. Results show that the proposed algorithm is a distributed optimization algorithm with high precision, high stability and high energy saving. Compared with one strategy that is not optimized, the operation strategy optimized by the proposed algorithm can save energy about 28.54% while realizing the dynamic hydraulic balance of the pipe network. Highlights: The generality of the algorithm in the distributed control architecture is improved. Hydraulic balance optimization problem of chilled pipe network is decoupled. ADMM with regular term solves distributed optimal operation problem of parallel pumps. ADMM saves energy 28.54%, realizing the dynamic hydraulic balance of the pipe network.